2013
DOI: 10.1007/s00464-013-3182-2
|View full text |Cite
|
Sign up to set email alerts
|

Modified laparoscopic and open splenectomy and azygoportal disconnection for portal hypertension

Abstract: The less invasive modified laparoscopic splenectomy and azygoportal disconnection group is a feasible, effective, and safe surgical procedure for liver cirrhosis patients with portal hypertensive bleeding and hypersplenism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…After decades of clinical practice and research, the role and status of devascularization in the treatment of gastric varices bleeding with portal hypertension has been fully established. [12][13][14] Gastric fundus venous hemorrhage can occur in a relatively wide area from the fundus of the stomach to the lower esophagus. Whether the upper digestive tract bleeds after devascularization depends mainly on the blockage of blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…After decades of clinical practice and research, the role and status of devascularization in the treatment of gastric varices bleeding with portal hypertension has been fully established. [12][13][14] Gastric fundus venous hemorrhage can occur in a relatively wide area from the fundus of the stomach to the lower esophagus. Whether the upper digestive tract bleeds after devascularization depends mainly on the blockage of blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…In June 2013, Jiang et al 23 reported 10 cases. In September 2013, Bai et al 24 reported 37 cases in their controlled study. In June 2014, Cheng et al 25 reported 204 cases.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure for laparoscopic splenectomy has been described. 10 Laparoscopic partial hepatectomy was performed as follows. First, the device for the modified Pringle maneuver, prepared as described elsewhere, 11 could be used to block the inflow of blood into the entire liver if necessary.…”
Section: Methodsmentioning
confidence: 99%
“…The entire spleen was removed through trocar D with an electromechanical morcellator (TSCS, Hangzhou, China) 10 ; spleen samples had a cylindrical appearance ( Figure 3 ). The tumor specimen was loaded into a specimen bag and removed though the enlarged umbilical incision, usually <5 cm, which was extended to a proper length along the linea alba, according to the size of the tumor.…”
Section: Methodsmentioning
confidence: 99%